Pre-concentration of heavy metals in aqueous environments using electrospun polymer nanofiber sorbents - Darko, Godfred (Rhodes University, Faculty of Science, Department of Chemistry, 2012)
This thesis presents an alternative approach for pre-concentrating heavy metals in aqueous environments using electro spun polymer nanofiber sorbents. The conditions for electrospinning polyethersulfone, polystyrene, polysulfone and polyamide-6 were optimized. The morphologies and porosities of the electrospun nanofibers were studied using SEM and BET nitrogen gas adsorptions. The nanofibers had mesoporous morphologies with specific surface areas up to 58 m2/g. The electro spun nanofiber sorbents were characterized in terms of their tunability for both uptake and release of heavy metals. The usability of the sorbent was also assessed. The sorbents showed fast adsorption kinetics for heavy metals Â« 20 min for As, Cu, Ni and Pb) in different aqueous environments. The adsorption characteristics of the sorbents best fitted the Freundlich isotherm and followed the first order kinetics. The efficiencies of adsorption and desorption of heavy metals on both imidazolyl-functionalized polystyrene and amino-functionalized polysulfone sorbents were more than 95% up to the fifth cycle of usage. Reusability improved dramatically (up to 10 runs of usage) when mechanically stable amino-functionalized nylon-6 electro spun nanofibers were used. The capacity of the amino-functionalized nylon-6 sorbent to pre-concentrate heavy metals compared very favourably with those of aqua regia and HN03+H202 digestions especially in less complex matrices. Due to their highly porous nature, the electro spun nanofibers exhibited high adsorption capacities (up to 50 mg/g) for heavy metal ions. The loading capacities achieved with the imidazolyl-functionalized sorbent were higher than those for amino-functionalized mesoporous silica and biomass-based sorbents. The electro spun nanofiber sorbents presents an efficient and cost effective alternative for preconcentrating heavy metals in aqueous environments.
Keywords: Heavy metals -- Absorption and adsorption -- Research; Nanochemistry -- Research; Polystyrene -- Research; Polyamides -- Research